A multiple-scenario assessment of the effect of a continuous-care, guideline-based decision support system on clinicians' compliance to clinical guidelines. Issue 4 (April 2015) - Shalom, Erez; Shahar, Yuval; Parmet, Yisrael; Lunenfeld, Eitan
<x xml:space="preserve">Abstract</x> Graphical abstract